Aftermaths : exile, migration, and diaspora reconsidered - Bullock, Marcus Paul, 1944-; Paik, Peter Yoonsuk (New directions in international studies., 2009)
Aftermaths offers compelling new ideas on exile, migration, and diaspora. Ten contributors-well-established scholars and promising new voices-working in different disciplines and drawing from diverse backgrounds present rich case studies from around the world. Seeking fresh perspectives on the movement of people and ideas, the essays take on a wide range of subjects such as the influence of religion upon diasporic consciousness, the conflict between the local and the transnational, the fate of historical tragedy in globalization, the reinvention of social bonds across migrations, and the agoni.